TESTING EDLINK'S ABILITY TO MANAGE BLENDED LEARNING - Nasrum, Akbar; Mashuri, Sufri; Subawo, Made (JME (Journal of Mathematics Education), 2024)
The main purpose of this research is to find out the advantages and disadvantages of the sevima edlink application through application in lectures using mixed methods. The advantages and disadvantages obtained are expected to be input for the university for the development of a better campus LMS. A good LMS will support the implementation of good MBKM through distance learning programs. In addition to finding out the advantages and disadvantages of Edlink, another important point is to involve students including lecturers involved to actively participate in using learning technology. This is one of the important points of this research.Â Tujuan utama dari penelitian ini adalah mencari tahu kelebihan dan kekurangan aplikasi sevima edlink melalui penerapan dalam perkuliahan yang menggunakan metode campuran. Kelebihan dan kekurangan yang diperoleh diharapkan dapat menjadi masukan bagi universitas demi pengembangan LMS kampus yang lebih baik. LMS yang baik akan mendukung terlaksananya MBKM yang baik melalui program belajar jarak jauh. Selain mencari tahu kelebihan dan kekurangan Edlink, poin penting lainnya adalah melibatkan mahasiswa termasuk dosen yang terlibat untuk ikut aktif dalam menggunakan teknologi pembelajaran. Hal ini yang menjadi salah satu poin penting dilakukannya penelitian ini.